Investigation of the potential of Glycyrrhiza glabra as a bioavailability enhancer of Vitamin B12 - Sharma, Priyanka; Pathak, Priyanka; Tyagi, Vidushi; Khan, Feroz; Shanker, Karuna; Darokar, Mahendra Pandurang; Pal, Anirban (Frontiers in Nutrition, 2022)
Vitamin B12 deficiency is prevalent among individuals globally. Inadequate consumption of B12 rich diet and low bioavailability (due to diet based/physiological factors) are linked to the deficiency of Vitamin B12 inside the body. Bioavailability enhancers augment the bioavailability of an ingested substance (drug/nutrient) thus increasing their concentration inside the body and maximizing their therapeutic benefits. In traditional medicine, Licorice (Glycyrrhiza glabra) finds utility in the treatment of various health conditions. Thus, the present study aimed to examine the potential of ethanolic extract obtained from G. glabra roots to enhance the bioavailability of Vitamin B12. The effect of ethanolic extract of G. glabra (GgEtOH) on intestinal absorption enhancement of B12 was assessed in vitro on Caco-2 and ex-vivo everted gut sac models. The influence of extract on the pharmacokinetics of Vitamin B12 was determined in vivo in Swiss albino mice. GgEtOH significantly enhanced the permeation (Papp) of B12 by 2-5 fold in vitro (25, 50, and 100 μg/ml concentrations) and ex-vivo (250 and 500 μg/ml concentrations). The pharmacokinetic parameters of B12 such as Cmax, AUC, Tmax, etc. were also significantly elevated in vivo upon oral administration of B12 (1 mg/kg dose) in combination with GgEtOH (100 and 1,000 mg/kg dose). These preliminary findings indicate that the ethanolic extract of G. glabra is capable of enhancing the bioavailability of Vitamin B12. To the best of our knowledge, this is the first report to demonstrate herbal extract-mediated enhancement of Vitamin B12 bioavailability through in vitro, ex vivo, and in vivo assays.